2016
DOI: 10.1158/2159-8290.cd-15-0675
|View full text |Cite
|
Sign up to set email alerts
|

Triggering the TCR Developmental Checkpoint Activates a Therapeutically Targetable Tumor Suppressive Pathway in T-cell Leukemia

Abstract: Cancer onset and progression involves the accumulation of multiple oncogenic hits, which are thought to dominate or bypass the physiologic regulatory mechanisms in tissue development and homeostasis. We demonstrate in T-cell acute lymphoblastic leukemia (T-ALL) that, irrespective of the complex oncogenic abnormalities underlying tumor progression, experimentally induced, persistent T-cell receptor (TCR) signaling has antileukemic properties and enforces a molecular program resembling thymic negative selection,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 49 publications
3
36
0
Order By: Relevance
“…This indicated that the strong/sustained TCR activation associated with the negatively selecting TCR- HY severely impaired leukemia maintenance. Consistent with this, stimulation of a TCR-negative cell line engineered to express the TCR-HY transgene by the DBY cognate antigen resulted in dose-dependent cell death [6]. Modern multi-agent chemotherapy has considerably improved T-ALL outcome.…”
mentioning
confidence: 95%
See 3 more Smart Citations
“…This indicated that the strong/sustained TCR activation associated with the negatively selecting TCR- HY severely impaired leukemia maintenance. Consistent with this, stimulation of a TCR-negative cell line engineered to express the TCR-HY transgene by the DBY cognate antigen resulted in dose-dependent cell death [6]. Modern multi-agent chemotherapy has considerably improved T-ALL outcome.…”
mentioning
confidence: 95%
“…We observed that co-expression of the TEL- JAK2 oncogene with a transgene encoding TCR-HY, which induces negative selection only in male mice, specifically compromised leukemia onset in males [4]. Importantly, in our new study [6], when leukemias obtained from females were transplanted in either male or female secondary recipients, only females succumbed to T-ALL. This indicated that the strong/sustained TCR activation associated with the negatively selecting TCR- HY severely impaired leukemia maintenance.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…It is thought that differences in binding strength and kinetics of activation are involved, as well as the cellular localization of TCR signaling components such as ERK ( 9 ). Such complexities suggest that manipulation of TCR signaling could have unpredictable effects on T-ALL cells, depending on signaling strength and stage of thymocyte maturation, but this issue had not been extensively studied in human T-ALL prior to the paper by Trinquand and colleagues in this issue ( 10 ).…”
mentioning
confidence: 99%